Determination of melamine in aquaculture feed samples based on molecularly imprinted solid‐phase extraction. Issue 20 (24th September 2015) - Lian, Ziru; Liang, Zhenlin; Wang, Jiangtao
Abstract : This research highlights the application of highly efficient molecularly imprinted solid‐phase extraction for the preconcentration and analysis of melamine in aquaculture feed samples. Melamine‐imprinted polymers were synthesized employing methacrylic acid and ethylene glycol dimethacrylate as functional monomer and cross‐linker, respectively. The characteristics of obtained polymers were evaluated by scanning electron microscopy, Fourier transform infrared spectroscopy and binding experiments. The imprinted polymers showed an excellent adsorption ability for melamine and were applied as special solid‐phase extraction sorbents for the selective cleanup of melamine. An off‐line molecularly imprinted solid‐phase extraction procedure was developed for the separation and enrichment of melamine from aquaculture feed samples prior to high‐performance liquid chromatography analysis. Optimum molecularly imprinted solid‐phase extraction conditions led to recoveries of the target in spiked feed samples in the range 84.6–96.6% and the relative standard deviation less than 3.38% ( n = 3). The aquaculture feed sample was determined, and there was no melamine found. The results showed that the molecularly imprinted solid‐phase extraction protocols permitted the sensitive, uncomplicated and inexpensive separation and pre‐treatment of melamine in aquaculture feed samples.